ANALISIS PENGARUH PARTISIPASI PENGGUNA, KAPABILITAS PERSONEL, PELATIHAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA SISTEM PENJUALAN TIKET PT DHARMA LAUTAN UTAMA - Dini Ayu Handayani; Bagus Kusuma Ardi; sutono - (LPPM STIE DHARMAPUTRA SEMARANG, 2021)
AbstractThis study aims to analyze the effect of user participation, personnel capabilities and training education on accounting Information Systems performance in the ticket sales system at the Dharma Lautan Utama Company. The sample in this study was 50 using the purposive sample method. Testing Hypothesis 1 (H1) resulted in user participation having a significant positive effect on accounting Information Systems performance. So that it can be interpreted the better user participation, the better the accounting Information Systems performance. Hypothesis 2 testing (H2) resulted in personnel capabilities having a significant positive effect on accounting Information Systems performance. So that it can be interpreted that the better the personnel capability, the better the accounting Information Systems performance. Hypothesis 3 testing (H3) results in training education having a significant positive effect on accounting Information Systems performance. So that it can be interpreted that the better the training education, the better the accounting Information Systems performance. Keywords: Performance, Accounting Information Systems, User Participation, Personal Capabilities, Training and Education Programs AbstrakPenelitian ini bertujuan menganalisis pengaruh partisipasi pengguna, kapabilitas personel dan Pelatihan terhadap kinerja SIA pada sistem penjualan tiket di PT. Dharma Lautan Utama. Sampel pada penelitian ini sejumlah 50 dengan menggunakan metode purposive sample. Pengujian Hipotesis 1 (H1) menghasilkan partisipasi pengguna berpengaruh positif signifikan terhadap Kinerja Karyawan. Sehingga dapat diintepretasikan semakin baik partisipasi pengguna, maka semakin baik kinerja Karyawan. Pengujian hipotesis 2 (H2) menghasilkan kapabilitas personel berpengaruh positif signifikan terhadap Kinerja Karyawan. Sehingga dapat diintepretasikan semakin baik kapabilitas personel, maka semakin baik kinerja Karyawan. Pengujian hipotesis 3 (H3) menghasilkan pelatihan berpengaruh positif signifikan terhadap Kinerja Karyawan. Sehingga dapat diintepretasikan semakin baik pelatihan, maka semakin baik kinerja Karyawan. Kata Kunci : Kinerja Karyawan, Partisipasi Pengguna, Kapabilitas Personal, Program Pelatihan, Sistem Informasi Akuntansi